Legal Aspects of the Blockchain Technology - Mendoza Munar, Lainiver; Riascos Diaz, Andrés Alberto (Law, State and Telecommunications Review, 2021)
Purpose – This study analyzes some relevant aspects of the role of public faith against the operability of the blockchain, as well as the incidence of this technology in relevant legal aspects such as privacy and the protection of personal data as fundamental rights in Colombia. Methodology- The research method is that of legal cybernetics, which studies the relationship between actions and their objectifying effects. In this case the action is the use of blockchain technology and its effects on the use of private information, as well as its purposes and consequences in the legal field based on a reflective relativism that is: adopting the disruptive changes that arise from technological uses in order to demonstrate how the classic concepts of law in commercial practices and commercial relations have currently changed, relativizing traditional legal constructions, which do not reach the regulation of these new practices, which become usual and obviously non-legal practices, that is, practices that appear spontaneously for the world of law, but which are already in place in social practices and thus although there is a legal denial and s it is essential for society to get out of these megatrends such as the use of mobile applications for transport services and the use of the blockchain(Ghersi, 2017). Findings – An analysis of the operation of the blockchain and the main legal implications was achieved, as well as identifying the associated legal risks in terms of contractual freedom, personal data protection and privacy rights. Practical Implications – The blockchain is a technology that is being used in the business field and in the relationships between individuals nowadays more and more frequently, however, as part of private law relations considered atypical for Colombian legislation this makes it necessary for those who They use, from various roles, to know the implications and risks in legal matters and the importance of managing in this regard.